Acute respiratory distress syndrome in mechanically ventilated patients with community-acquired pneumonia. Issue 3 (29th March 2018) - Cilloniz, Catia; Ferrer, Miquel; Liapikou, Adamanthia; Garcia-Vidal, Carolina; Gabarrus, Albert; Ceccato, Adrian; Puig de La Bellacasa, Jorge; Blasi, Francesco; Torres, Antoni
Our aim was to assess the incidence, characteristics, aetiology, risk factors and mortality of acute respiratory distress syndrome (ARDS) in intensive care unit (ICU) patients with community-acquired pneumonia (CAP) using the Berlin definition. We prospectively enrolled consecutive mechanically ventilated adult ICU patients with CAP over 20 years, and compared them with mechanically ventilated patients without ARDS. The main outcome was 30-day mortality. Among 5334 patients hospitalised with CAP, 930 (17%) were admitted to the ICU and 432 required mechanical ventilation; 125 (29%) cases met the Berlin ARDS criteria. ARDS was present in 2% of hospitalised patients and 13% of ICU patients. Based on the baseline arterial oxygen tension/inspiratory oxygen fraction ratio, 60 (48%), 49 (40%) and 15 (12%) patients had mild, moderate and severe ARDS, respectively. Streptococcus pneumoniae was the most frequent pathogen, with no significant differences in aetiology between groups. Higher organ system dysfunction and previous antibiotic use were independent risk factors for ARDS in the multivariate analysis, while previous inhaled corticosteroids were independently associated with a lower risk. The 30-day mortality was similar between patients with and without ARDS (25% versus 30%, p=0.25), confirmed by propensity-adjusted multivariate analysis. ARDS occurs as a complication of CAP in 29% of mechanically ventilated patients, but is not related to the aetiology or mortality. In mechanically ventilated patients with community-acquired pneumonia, ARDS based on the Berlin criteria was not related to aetiology or mortality http://ow.ly/BDMm30izoCN